US law enforcement’s role in victim compensation dissemination - Davis, Robert C. (International review of victimology, 2021)
Victim compensation programs seek to alleviate adverse effects of victimization and repay victim losses. A few studies have concluded that US compensation programs are under-utilized because victims are unaware of such programs and police officers overlook sharing the information. The present study sought to further explore this issue from the perspective of state compensation directors and police executives. Survey respondents were asked their opinions about police officers’ basic knowledge of victims’ compensation programs, reasons for under-utilization of the programs, and the most effective ways to inform victims of their right to compensation. Surveys were administered to 38 state compensation directors and 23 law enforcement executives from across the US. Survey results confirmed the belief that many eligible victims are not receiving compensation and that better training of patrol officers on compensation eligibility and benefits was needed. However, just one in 10 of the state directors implicated police failure to notify victims as a major reason for victims not filing claims. The consensus of both police administrators and state compensation directors was that, while patrol officers should be tasked with providing basic notification of compensation availability, it is important that victim advocates and police detectives follow up with more detailed information in the days following victimization. Policy implications and future directions for research are discussed in light of the findings.